Aprendizaje de las ecuaciones diferenciales desde un enfoque cualitativo - Caicedo, Edinson; Chacón, Gerardo Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this research was to design and validate a didactic model for learning differential equations with emphasis on qualitative methods and based on the quasi-empirical conception of mathematics. A qualitative methodology was used, five engineering students from Antonio Nariño University belonging to a course of differential equations participated. Class plans were used as instruments. The results obtained show that students feel motivated and interested, it was observed that the methodology applied based on problem solving, using conjectures from the construction of the model to reach the final solution and the use of technology to study qualitative methods and numerical favors the understanding of the course contents. The didactic model offers a route and resources that promote mathematical activity in the courses of differential equations and that can be replicated in other courses.